Analisis Kualitas Pelayanan dalam Meningkatkan Kepuasan Nasabah Penerima Manfaat Bank Wakaf Mikro (BWM) Mawaridussalam - Pradesyah, Riyan; Munawaroh; M. Radian Syah; Asmawarna Sinaga; Safira Khoirunnisa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the partial and simultaneous influence of the variables Reliability (X1), Tangibles (X2), Responsiveness (X3), and Assurance (X4) on customer satisfaction (Y) beneficiaries of the mawaridussalam micro waqf bank. The respondents used in the study were 100 people, and the research approach used in completing the research was a quantitative approach. The analysis tool used in data processing is SmartPLS, the findings obtained in this study, that there is a partial influence of the Reliability (X1) and Responsiveness (X3) variables on customer satisfaction (Y) of the beneficiaries of the mawaridussalam micro waqf bank. Meanwhile, the variables Tangibles (X2) and Assurance (X4) have no influence on the customer satisfaction variable (Y). Simultaneously, there is a strong influence of the variables Reliability (X1), Tangibles (X2), Responsiveness (X3), and Assurance (X4) on the variables of Customer Satisfaction (Y) of the beneficiaries of the mawaridussalam micro waqf bank.